Copper/P(tBu)3‐Mediated Regiospecific Synthesis of Fused Furans and Naphthofurans. (20th December 2016) - Naveen, Togati; Deb, Arghya; Maiti, Debabrata
Abstract: A novel [3+2] cycloaddition between a variety of cyclic ketones and diverse olefins or alkynes can be effectively promoted by copper in combination with the tri‐ tert ‐butylphosphine [P( t Bu)3 ] ligand. This protocol exhibits excellent selectivity and provides an exemplary set of fused heterocycles in good to excellent yields. Present strategy also represents an extremely simple and atom‐economic way to construct substituted fused furans and naphthofurans from readily available starting materials under mild reaction conditions. The utility of the method is further demonstrated by the synthesis of chiral furans from ( R )‐(−)‐carvone and ( S )‐(+)‐carvone. A plausible mechanism involving the oxidative radical cyclization has been suggested based on experimental observations.